The dynamic nature of the K-Ras/calmodulin complex can be altered by oncogenic mutations. (December 2021) - Abdelkarim, Hazem; Leschinsky, Nicholas; Jang, Hyunbum; Banerjee, Avik; Nussinov, Ruth; Gaponenko, Vadim
Abstract: Oncogenic mutant K-Ras promotes cancer cell proliferation, migration, invasion, and survival by assembling signaling complexes. To date, the functional and structural roles of K-Ras mutations within these complexes are incompletely understood despite their mechanistic and therapeutic significance. Here, we review recent advances in understanding specific binding between K-Ras and the calcium sensor calmodulin. This interaction positively and negatively regulates diverse functions of K-Ras in cancer, suggesting flexibility in K-Ras/calmodulin complex formation. Also, structural data suggest that oncogenic K-Ras likely samples several conformational states, influencing its distinct assemblies with calmodulin and with other proteins. Understanding how K-Ras interacts with calmodulin and with other partners is essential to discovering novel inhibitors of K-Ras in cancer. Graphical abstract: The assembly of K-Ras GTPase and calmodulin regulates signal transduction in cancer and remains the focus of intense research. This review highlights the key features of the interaction between wild type K-Ras and calmodulin and suggests that novel regulatory mechanisms can be discovered from studies of calmodulin complexes with oncogenic mutants of K-Ras. Image 1 Highlights: Calmodulin (CaM), a calcium-binding protein, regulates cellular signaling. Oncogenic K-Ras is an essential signaling protein in cancer. Calmodulin interacts with oncogenic K-Ras selectively and modulates its activity. Insights into K-Ras–CaM interaction may help design and selective drugs.